Vicious and virtuous epistemic egoism - Masakayan, Nicolo M. (UP Los Baños Journal, 2021)
Epistemic egoist are individuals who believe that there are no prima facie reasons why we should accept testimony. In this paper I examine the question "is epistemic egoism an intellectual virtue?" I assert that a variant of epistemic egoism, called weak epistemic egoism, satisfies reliabilist conditions for intellectual virtue. I also assert that extreme epistemic egoism, characterized as a blanket rejection of all testimony is an intellectual vice. I also examine the possibility that extreme epistemic egoism is an intellectual virtue in rare situations. I argue that extreme epistemic egoism can be valuable, bit not for strictly epistemic reasons.